Strengthening Human Resources, Infrastructure, and Services on the Performance of Wosu Community Health Center Employees, West Bungku District, Morowali Regency - Fatmala, Ririn; AC, Ahmad; Rizal, Samsul (Manunggal Halim Jaya, 2024)
This research aims to determine the influence of resources on employee performance at the Wosu Community Health Center UPTD, West Bungku District, Morowali Regency. Infrastructure for Employee Performance at UPTD Wosu Health Center, West Bungku District, Morowali Regency, and Services for Employee Performance at UPTD Wosu Health Center, West Bungku District, Morowali Regency. According to Nabawi (2019), employee performance achievements are the result of work in carrying out tasks assigned by the work unit organization. Alternatively, the quality and quantity performance achieved by an employee in carrying out his duties by the responsibilities given to him (Fitri Handayani et al., 202). So, indicators of a person's performance achievements are determined based on norms, standard operating procedures, criteria, and functions that have been determined or are in force (Wijaya, 2017). This type of research is descriptive with a quantitative approach using a questionnaire as a source of data collection. This research uses an explanatory research method using multiple linear analysis techniques. The results of the research show that: 1. Human Resources have a positive and significant effect on employee performance; this shows that the presence of good and quality human resources can improve employee performance; 2. Infrastructure has a positive and significant effect on employee performance, which shows that the availability of complete Infrastructure can encourage improving employee performance. 3. Service has a positive and significant effect on employee performance; this shows that providing good service can influence the quality of service received by patients, which is an effective strategy for improving the performance of employees who are satisfied with their performance.